Characterization of immunoglobulin G antibodies to Plasmodium falciparum sporozoite surface antigen MB(2) in malaria exposed individuals - Nguyen, Thanh V (BioMed Central, 2009)
BACKGROUND: MB2 protein is a sporozoite surface antigen on the human malaria parasite Plasmodium falciparum. MB2 was identified by screening a P. falciparum sporozoite cDNA expression library using immune sera from a protected donor immunized via the bites of P. falciparum-infected irradiated mosquitoes. It is not known whether natural exposure to P. falciparum also induces the anti-MB2 response and if this response differs from that in protected individuals immunized via the bites of P. falciparum infected irradiated mosquitoes. The anti-MB2 antibody response may be part of a robust protective response against the sporozoite. METHODS: Fragments of polypeptide regions of MB2 were constructed as recombinant fusions sandwiched between glutathione S-transferase and a hexa histidine tag for bacterial expression. The hexa histidine tag affinity purified proteins were used to immunize rabbits and the polyclonal sera evaluated in an in vitro inhibition of sporozoite invasion assay. The proteins were also used in immunoblots with sera from a limited number of donors immunized via the bites of P. falciparum infected irradiated mosquitoes and plasma and serum obtained from naturally exposed individuals in Kenya. RESULTS: Rabbit polyclonal antibodies targeting the non-repeat region of the basic domain of MB2 inhibited sporozoites entry into HepG2-A16 cells in vitro. Analysis of serum from five human volunteers that were immunized via the bites of P. falciparum infected irradiated mosquitoes that developed immunity and were completely protected against subsequent challenge with non-irradiated parasite also had detectable levels of antibody against MB2 basic domain. In contrast, in three volunteers not protected, anti-MB2 antibodies were below the level of detection. Sera from protected volunteers preferentially recognized a non-repeat region of the basic domain of MB2, whereas plasma from naturally-infected individuals also had antibodies that recognize regions of MB2 that contain a repeat motif in immunoblots. Sequence analysis of eleven field isolates and four laboratory strains showed that these antigenic regions of the basic domain of the MB2 gene are highly conserved in parasites obtained from different parts of the world. Moreover, anti-MB2 antibodies also were detected in the plasma of 83% of the individuals living in a malaria endemic area of Kenya (n = 41). CONCLUSION: A preliminary analysis of the human humoral response against MB2 indicates that it may be an additional highly conserved target for immune intervention at the pre-erythrocytic stage of P. falciparum life cycle.